Sosialisasi Disaster Management Bagi Ibu Rumah Tangga - Dwi Putra Buana Sakti; Lalu Suparman; Hermanto Hermanto; Junaidi Sagir (Universitas Mataram, 2021)
The concept of disaster management is growing after realizing the impact caused by the disaster. One of the areas on the island of Lombok that was affected by the 2018 earthquake is the North Lombok Regency. Located in an area prone to earthquakes, efforts are needed to minimize the risk of a disaster occurring. One of them is through community service activities in the form of disaster management socialization to housewives. Housewives are deemed necessary to be given socialization because the phenomenon shows that the involvement of housewives in disaster management is still minimal. In several disaster events, it is seen that the role of housewives is more often the object of disaster management. Women are still considered as the weak and do not have any power when a disaster occurs. Referring to this phenomenon, this socialization is aimed at educating housewives about disaster management in order to increase their knowledge and capacity about disaster management. This socialization was carried out using lecture and discussion methods related to the following materials: (i) disaster management; (ii) disaster risk, and (iii) regional disaster management organization. The output of this activity is an increase in the understanding and capacity of housewives about disaster management, disaster risk and knowledge of disaster management organizations in the regions.